New commercial behaviour as a reason of social and economic changes of divided towns on the Polish-German and Polish-Czech borders - Katarzyna Kulczyńska; Roman Matykowski; Elżbieta Bilska-Wodecka (Rozwój Regionalny i Polityka Regionalna)
The end of the First World War saw a rebirth of the Polish state, but with indeterminate borders. As a result of a conflict between Poland and Czechoslovakia about Cieszyn Silesia, in February 1919 this area, including the town of Cieszyn, was temporarily divided (its part on the left bank of the Olza went to Czechoslovakia). Similarly, after the Second World War the new Polish-German border ran along the Lusatian Nysa and Oder rivers. Also in this case several split towns were created (including Görlitz-Zgorzelec, Gubin-Guben, and Frankfurt on the Oder – Słubice). Besides, despite the strong dividing /separating function of the border, some of the towns with border crossings started to expand towards the state border (e.g. Kudowa-Zdrój and Nachod). After the political transformation of the late 1980s and early ‘90s, split and border towns experienced significant changes in their demographic structures as well as in their economies and services. Thus, they started developing various complementary functions (especially shopping and some services) for the residents of the other side of the border. Demographic changes are most readily visible in the German parts of the split towns, in which shrinkage has accelerated after the unification of Germany. This process involves, among other things, a heavy outflow of inhabitants, primarily young and better educated, to western lands and a steep slump in the total fertility rate. Still, the most important changes observed in the split towns over the last two decades have been consumer behaviour patterns determined, among other things, by differences in prices in the neighbouring states. They involve frequent crossings of the state border to buy goods and services cheaper than in the home town. The chief places intended to serve consumers from the other side of the border are mostly bazaars (on the Polish side) and a network of specialised service facilities.